In vitro culture of white lupin embryos as a stage for SSD technique - Ogrodowicz, Piotr; Mikołajczak, Krzysztof; Kuczyńska, Anetta; Kaczmarek, Zygmunt; Ćwiek-Kupczyńska, Hanna; Surma, Maria; Adamski, Tadeusz; Święcicki, Wojciech; Barzyk, Paweł; Trzeciak, Renata; Kempa, Michał (Polish Journal of Agronomy, 2021)
White lupin is an important source of proteins, the content of which amounts to 36–40% in its seeds. Breeding of new varieties usually takes several years. The present study aimed to shorten the breeding cycle by applying the single-seed descent technique together with in vitro culture of embryos dissected from immature seeds. The effects of temperature on embryo development were studied in indeterminate vs. determinate varieties in in vitro culture using the following temperature regimes: (1) 8 °C; (2) 16 °C in the first week, then 8 °C; (3) 20 °C in the first week, then 20/18 °C; and (4) 16 °C throughout the culture period. The embryos were cultured on the standard Murashige and Skoog medium. The observed growth rate of plantlets as well as the survival of plants ex vitro showed that at lower temperatures (8–16 °C) the plants developed slowly, but their ex vitro survival rate was higher compared to those grown at a higher temperature (20 °C). In addition, the results indicated that the in vitro embryo development rate of determinate varieties is significantly lower than that of indeterminate varieties.